2014
DOI: 10.1016/j.jhep.2014.07.027
|View full text |Cite
|
Sign up to set email alerts
|

Global epidemiology and genotype distribution of the hepatitis C virus infection

Abstract: The treatment of chronic hepatitis C virus (HCV) infection has the potential to change significantly over the next few years as therapeutic regimens are rapidly evolving. However, the burden of chronic infection has not been quantified at the global level using the most recent data. Updated estimates of HCV prevalence, viremia and genotypes are critical for developing strategies to manage or eliminate HCV infection. To achieve this, a comprehensive literature search was conducted for anti-HCV prevalence, virae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

40
1,632
15
86

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 1,720 publications
(1,773 citation statements)
references
References 45 publications
40
1,632
15
86
Order By: Relevance
“…Our results are comparable with results of other investigator who found that the onset of DILI ranged from 13 days to 58 days (median, 26 days) after initiation of treatment [36]. And in another study, the median latent period for developing DILI was found to be 19 [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] days [37].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our results are comparable with results of other investigator who found that the onset of DILI ranged from 13 days to 58 days (median, 26 days) after initiation of treatment [36]. And in another study, the median latent period for developing DILI was found to be 19 [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] days [37].…”
Section: Discussionsupporting
confidence: 88%
“…WHO estimates that 3% of the world's population is infected with HCV and that more than 170 million chronic carriers are at risk of developing liver cirrhosis and/or liver cancer [9]. In Egypt, chronic hepatitis C virus (HCV) infection is a major cause of liver cirrhosis and liver cancer [10]. Hepatitis B is also one of the major health problems.…”
Section: Introductionmentioning
confidence: 99%
“…The increasing incidence of IBM in Japan is in strong contrast to the decreasing incidence in HCV infections 66, 67, 68. Moreover, countries with relatively high incidence rates of HCV infections belong to the regions that are stricken the least by IBM 26, 30, 61, 69, 70, 71. It is conceivable that nonpersistent contact with a pathogen suffices to trigger autoimmunity 72.…”
Section: Pathomechanisms In Ibmmentioning
confidence: 97%
“…HCV infection is one of the major reasons for chronic liver diseases and if not treated on time, often leads to liver cirrhosis and hepatocellular carcinoma. It is estimated that approximately 71 million people are chronically infected with HCV worldwide [2]. HCV is classified into 7 genotypes (GTs), the most common GT globally being GTs 1 and 3 [3].…”
Section: Introductionmentioning
confidence: 99%